Linguistic Identity and Social Roles in the Film Green Book - Wardana, Inas Abiyyu; Fauziati, Endang (Universitas Muhammadiyah Mataram, 2025)
This study explores how language reflects and negotiates cultural identity, power, and social relations through an ethnographic analysis of communication in the 2018 film Green Book. The research is grounded in the need to understand how communication functions as a bridge across cultural and racial divisions, particularly in media representations set within historically segregated contexts. Employing a qualitative content analysis design, the study applies Dell Hymes’ S.P.E.A.K.I.N.G. model to analyze the main character’s communicative practices throughout the film. Focusing on three key components—setting, participants, and ends—the analysis reveals a significant transformation in the character’s speech, evolving from culturally insensitive and informal language toward more empathetic, respectful, and contextually appropriate communication. These changes reflect a broader process of identity negotiation and cultural awareness shaped by dynamic social interactions. The findings contribute to the field of sociolinguistics by illustrating how communicative competence is constructed and reshaped in intercultural contexts, and they also offer insights for media and cultural studies on how film can serve as a site for representing and critiquing social norms and values.